2016
DOI: 10.1111/jgs.14297
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Outcomes of Older Adults After Undergoing Rehabilitation for Hip Fracture

Abstract: Objectives To determine the contribution of cognitive impairment, prefracture functional impairment, and treatment as predictors of functional status and mobility 6 months after discharge from rehabilitation for older adults with hip fracture. Design Longitudinal. Setting Inpatient rehabilitation units of two community hospitals. Participants Adults with hip fractures aged 65 and older who were discharged from a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
61
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 38 publications
7
61
0
Order By: Relevance
“…Although median LOS was 1 day longer than that the pathway required, it was shorter than what reported in most similar studies (22 days vs 28–30) [6, 2427]. We also found a significant reduction of pain, bedsores, and number of patients with urinary catheter on discharge: these conditions are rarely reported as HF rehabilitation outcomes, although they may impact on clinical complications as well as on functional gain [9, 28].…”
Section: Discussionmentioning
confidence: 71%
“…Although median LOS was 1 day longer than that the pathway required, it was shorter than what reported in most similar studies (22 days vs 28–30) [6, 2427]. We also found a significant reduction of pain, bedsores, and number of patients with urinary catheter on discharge: these conditions are rarely reported as HF rehabilitation outcomes, although they may impact on clinical complications as well as on functional gain [9, 28].…”
Section: Discussionmentioning
confidence: 71%
“…Most of the patients did not reach their pre‐fracture level of mobility . Pre‐facture functional impairment seems to be associated with poor function and mobility in short‐ and mid‐term follow up . Other factors that are associated with poor functional outcome after the different observation periods (6–12 months) are increasing age, living in an institution, poor mental status, female sex, trochanteric fractures, a higher degree of comorbidity and poor functional status after discharge .…”
Section: Introductionmentioning
confidence: 95%
“…8,9 Pre-facture functional impairment seems to be associated with poor function and mobility in shortand mid-term follow up. 7,[10][11][12] Other factors that are associated with poor functional outcome after the different observation periods (6-12 months) are increasing age, 7,8,12,13 living in an institution, 13 poor mental status, 7,12,14,15 female sex, 12 trochanteric fractures, 7 a higher degree of comorbidity 8 and poor functional status after discharge. 13 There is only one retrospective cohort study with functional long-term follow up that reported the Barthel Index 4.9 years after hip fracture.…”
Section: Introductionmentioning
confidence: 99%
“…7 Postfracture functional decline has important implications for quality of life and healthcare costs, 8 and it leads to institutionalization in up to 20% of patients. 7 Prior studies in community-dwelling older adults who have sustained hip fracture have included functionally heterogeneous populations 5,[9][10][11][12] and have established that the strongest risk factor for postfracture functional decline is prefracture disability. 5,[9][10][11][12] However, 60% of hip fractures occur in persons without preexisting disability, 13,14 emphasizing the need to understand what factors predict functional decline in this important subgroup.…”
mentioning
confidence: 99%
“…7 Prior studies in community-dwelling older adults who have sustained hip fracture have included functionally heterogeneous populations 5,[9][10][11][12] and have established that the strongest risk factor for postfracture functional decline is prefracture disability. 5,[9][10][11][12] However, 60% of hip fractures occur in persons without preexisting disability, 13,14 emphasizing the need to understand what factors predict functional decline in this important subgroup. Other risk factors for functional decline are age, 11,15 multimorbidity, 9 cognitive impairment, 9,12,16,17 and in-hospital delirium.…”
mentioning
confidence: 99%